Delivery of dual miRNA through CD44-targeted mesoporous silica nanoparticles for enhanced and effective triple-negative breast cancer therapy. (22nd April 2020) - Ahir, Manisha; Upadhyay, Priyanka; Ghosh, Avijit; Sarker, Sushmita; Bhattacharya, Saurav; Gupta, Payal; Ghosh, Swatilekha; Chattopadhyay, Sreya; Adhikary, Arghya
Abstract : Cationic Mesoporous silica Nanoparticle coated with hyaluronic acid conjugated polymer (HA-Dual miRNA Np) facilitated enhanced dual miRNA loading, efficient delivery and significantly inhibited tumor growth as well as retarded metastasis in triple-negative breast cancer. Abstract : The development of new therapeutic strategies to target triple-negative breast cancer (TNBC) is in much demand to overcome the roadblocks associated with the existing treatment procedures. In this regard, therapies targeting the CD44 receptor have drawn attention for more than a decade. MicroRNAs (miRNAs) modulate post-transcriptional gene regulation and thus, the correction of specific miRNA alterations using miRNA mimics or antagomiRs is an emerging strategy to normalize the genetic regulation in the tumor microenvironment. It has been acknowledged that miR-34a is downregulated and miR-10b is upregulated in TNBC, which promotes tumorigenesis and metastatic dissemination. However, there are a few barriers related to miRNA delivery. Herein, we have introduced tailored mesoporous silica nanoparticles (MSNs) for the co-delivery of miR-34a-mimic and antisense-miR-10b. MSN was functionalized with a cationic basic side chain and then loaded with the dual combination to overexpress miR-34a and downregulate miR-10b simultaneously. Finally, the loaded MSNs were coated with an hyaluronic acid-appended PEG-PLGA polymer for specific targeting. The cellular uptake, release profile, and subsequent effect in TNBC cells were evaluated. In vitro and in vivo studies demonstrated high specificity in TNBC tumor targeting, leading to efficient tumor growth inhibition as well as the retardation of metastasis, which affirmed the clinical application potential of the system.